Optimization of the Extrusion Process in the Production of Compound Feeds for Dairy Cows - Rabiga Kassymbek; Auyelbek Iztayev; Tahir Balevi; Urishbay Chomanov; Gulzhan Zhumaliyeva; Assiya Shoman (Ital Publication, 2023)
The paper proposes a way of enriching the composition of mixed fodder by combining two promising technologies with known effects: inclusion of germinated grain in the composition and extrusion. Crude and digestible protein, fiber, fat, and mineral elements Ca, K, Na, and P were studied. Inclusion of sprouted grain into mixed fodder and subsequent extrusion contribute to improvements in taste qualities, increased edibility, and assimilation of mixed fodder, as well as nutritive value. Taking into account the obtained knowledge about the influence of temperature regime and content of germinated triticale grain in mixed fodder production, it is advisable to continue research to adapt the technology and develop formulations for different types of animals and farm birds. The purpose of the study was to optimize the process of extrusion of sprouted triticale grain in order to reduce energy consumption and obtain high-quality extrudates. To achieve this goal, the following tasks were set: to analyze the regime factors affecting the fat content based on the optimization of technological modes of extrusion. To optimize the technology of extrusion of triticale grain of the Kozha variety, the fat content was chosen as the target function. Optimization of the technology of extrusion of triticale grain of the Kozha variety was carried out by the method of nonlinear programming. The following optimal technological modes of grain extrusion were obtained: The content of sprouted triticale grain is 15%, and the extrusion temperature is 140°C. With these optimal grain processing modes, the target function was 1.12%. The practical significance of the technology of the production of compound feeds with the use of extrusion in order to improve the quality and increase the shelf life. Doi: 10.28991/ESJ-2023-07-05-08 Full Text: PDF